The Relationship between University Students’ Training in Computing and their Motivation to Utilize ICT Resources in Learning in Selected Universities in Nakuru County, Kenya - Njagi, Kageni; Chemwei, Bernard; Ogoala, Leo B. (Advances in Social Sciences Research Journal, 2015)
Over the past few years, the use of information and communication technologies (ICT) in education has grown rapidly. The benefits of ICT adoption are evident. However, it is a known fact that teachers face many challenges in integrating ICTs in their teaching to enhance student learning. Based on a study of selected universities in Kenya, this paper examines the relationship between university students’ training in computing and their motivation to use ICT resources to learn. The study was guided by Rogers Diffusion of Innovations theory of 2003 which addresses change levels that teachers progress through in technology integration. Purposive sampling technique was used to select five universities that offer Bachelor of Education degree and 404 respondents who participated in the study. Data was collected using a questionnaire. The data collected was analysed descriptively with the help of the SPSS computer program version 20.0 and presented in the form of frequencies, means, standard deviation and percentages. The inferential statistics used to determine relationships among variables was the Pearson Moment Correlation. A p-value of less than 0.05 was interpreted as significant. The results of the study indicated that there was a significant relationship between university students’ level of training and their motivation to use ICT resources for learning. Based on the findings, it is recommended that ICT integration be made part of undergraduate training in universities in order to equip future educators with ICT skills and that higher education institutions should provide in-service training on ICTs for teachers. The study contributes vital knowledge on the challenges of integration of ICT in institutions of higher education in Kenya. This will help policy makers to come up with strategies to ensure ICT is integrated in learning institutions to enhance learning outcomes and improve the quality of education. Keywords: Bachelor, Education, Computing, Kenya, Teacher Training, Motivation, Integration, Universities, ICT